Segmental approach to lung volume reduction therapy for emphysema patients - Bandyopadhyay, Sourish; Henne, Erik; Gupta, Avina; Barry, Robert; Snell, Greg; Strange, Charlie; Herth, Felix (Respiration, 2015)
Emphysema is often distributed heterogeneously throughout the lungs, even at the segmental level. It is important for interventional lung volume reduction therapies to target and treat the most diseased regions of the lung while preserving the less diseased functional regions. Identification and determination of the severity of emphysema can be done using the various quantification measures reviewed in this article. However, all of these measures are similar in what they quantify and are equally good indicators of emphysema. The tissue/air ratio was chosen for our purposes. Software capable of quantifying emphysema severity at the segmental level exists, and can be utilized to identify the most diseased segments while following anatomical boundaries. The segmental heterogeneity index is a new measure being introduced to help quantify differences in emphysema severity at the segmental level. The goal of segmental targeting is to improve efficacy and safety outcomes of vapor ablation patients. The Sequential Staged Treatment of Emphysema with Upper Lobe Predominance (STEP-UP, NCT01719263) trial is currently enrolling patients with upper lobe heterogeneous emphysema using these techniques.